2020
DOI: 10.3390/molecules25245857
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Population in Host with Metabolic Syndrome during Administration of Chitosan and Its Derivatives

Abstract: Chitosan and its derivatives can alleviate metabolic syndrome by different regulation mechanisms, phosphorylation of AMPK (AMP-activated kinase) and Akt (also known as protein kinase B), suppression of PPAR-γ (peroxisome proliferator-activated receptor-γ) and SREBP-1c (sterol regulatory element–binding proteins), and translocation of GLUT4 (glucose transporter-4), and also the downregulation of fatty-acid-transport proteins, fatty-acid-binding proteins, fatty acid synthetase (FAS), acetyl-CoA carboxylase (acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 125 publications
1
17
0
Order By: Relevance
“…The inner mucus layer can separate the intestinal epithelia and microbes in the GI tract, preventing bacterial translocation and subsequent systemic inflammation [ 215 ]. The upregulated mucins mediated by SCFAs from the healthy gut microbiota can supply energy for specific beneficial mucin-degrading bacteria (e.g., Akkermansia muciniphila ), resulting in expanded microbiota outer mucus layer [ 11 , 215 ]. In summary, the mucus layer serves as the first barrier of defense against exogenous pathogens.…”
Section: Gut Microbiota and Colonization Resistance Against Enteric Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inner mucus layer can separate the intestinal epithelia and microbes in the GI tract, preventing bacterial translocation and subsequent systemic inflammation [ 215 ]. The upregulated mucins mediated by SCFAs from the healthy gut microbiota can supply energy for specific beneficial mucin-degrading bacteria (e.g., Akkermansia muciniphila ), resulting in expanded microbiota outer mucus layer [ 11 , 215 ]. In summary, the mucus layer serves as the first barrier of defense against exogenous pathogens.…”
Section: Gut Microbiota and Colonization Resistance Against Enteric Infectionsmentioning
confidence: 99%
“…Chitin is a biocompatible and biodegradable polysaccharide extracted from crustaceans, fungi, and insects [ 11 ]. Chitin can be converted into its deacetylated derivative, chitosan [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, COS can be easily absorbed through intestinal epithelium and quickly enters systemic circulation. It is shown that COS can enhance the phagocytic activity of macrophages by a mechanism related to nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, which induces nitric oxide synthase (i-NOS) [ 14 16 ]. Several studies have demonstrated protective effects of COS on damaged cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of chitin are crustaceans such as shrimp, crabs, and lobster. The chemical structure of chitin is similar to that of cellulose, having a hydroxyl group in each monomer substituted with an acetylamine group [ 17 , 60 , 61 ].…”
Section: Natural Polymers With Antibacterial and Bacteriostatic Prope...mentioning
confidence: 99%